36/#157 Enhanced recovery after surgery in open abdominal hysterectomy for malignant and benign disease: a randomised control trial. (4th December 2022) - Rajaram, Shalini; Sharma, Shweta; Gupta, Bindiya; Tyagi, Asha; Jain, Sandhya
Abstract : Objectives: Enhanced recovery after surgery (ERAS) is a multidisciplinary protocol that incorporates several perioperative components To compare perioperative outcomes and patient satisfaction in ERAS versus conventional management in a tertiary care setting. Methods: Sixty women who underwent hysterectomy through the open abdominal route for benign and malignant indications were recruited and randomized to two groups; ERAS vs. conventional. Sample size was calculated after fixing Type I error at 5% and power of study at 95%, assuming a standard deviation of 20%. Postoperative recovery, pain, hospital stay, complications and readmissions and patient satisfaction scores were analysed. Compliance to individual components and overall compliance was calculated.(CTRI/2020/02/023431) Results: Duration of hospital stay was shorter in ERAS group: 3.87±1.25 vs 5.60±1.18 days (p-value=0.001) in benign cases and 5.27±2.34 vs 6.33±1.29 days( p-value=0.01) in malignancy. Decreased time to ambulation (p <0.001), time to resumption of enteral feeding ( p=0.022 and 0.002), passage of flatus( p=0.002 and 0.028), stool(p< 0.001 and p=0.003)and lower pain scores (p-value<0.001) were seen in benign and malignant cases on ERAS protocol. Complications were comparable in ERAS vs. conventional protocols for Grade 1 (p-value=0.359), Grade 2(p-value=1.000) and Grade 3(p-value=0.125). Patient satisfaction scores and readmissions between the two groups were comparable. Conclusions: This trial showed a significant decrease in hospital stay, early ambulation, resumption of oral feeds, bowel motility and lower pain scores with ERAS protocol. Patient satisfaction scores did not differ between ERAS and conventional protocols and adoption of ERAS did not increase postoperative complications and readmissions.